Evaluation of epigenetic methylation biomarkers for the detection of colorectal cancer using droplet digital PCR - J. Petit; G. Carroll; J. Zhao; E. Roper; P. Pockney; R. J. Scott (Scientific Reports, 2023)
Abstract Colorectal cancer (CRC) is the third most common cancer worldwide. Screening programs allow early diagnosis and have improved the clinical management of this disease. Aberrant DNA methylation is increasingly being explored as potential biomarkers for many types of cancers. In this study we investigate the methylation of ten target genes in 105 CRC and paired normal adjacent colonic tissue samples using a MethylLight droplet digital PCR (ML-ddPCR) assay. Receiver operator characteristic (ROC) curves were used to determine the diagnostic performance of all target genes individually and in combination. All 515 different combinations of genes showed significantly higher levels of methylation in CRC tissue. The combination of multiple target genes into a single test generally resulted in greater diagnostic accuracy when compared to single target genes. Our data confirms that ML-ddPCR is able to reliably detect significant differences in DNA methylation between CRC tissue and normal adjacent colonic tissue in a specific selection of target genes.